COMPOSITE MATRIX POLYESTER REINFORCE FIBRESKIN GELAM; PREPARATION AND MECHANICAL PROPERTIES - Mataram, Agung; Rizal, Samsul; Zamheri, Ahmad (Politeknik Negeri Sriwijaya, Indonesia, 2015)
Gelam (melaleuca leucandendra) is one plant that is widely available in South Sumatra potential into cellulose extraction. His plant is widely used for building materials and wood products processed the rest of the powder timber furniture industry. While, the skin of this plant is not used for anything. In fact, fromÂ the structure of the skin that have fiber, skin of gelamÂ has the potential to be a valuable product, one of them with a matter in the form of composite reinforcement. While today's technology demands urgent environmental friendly technology product makers, especially friendly to the environment. The analysis conducted in this study utilizes softwood bark fiber serves as reinforcement to resin volume fraction ratio : Resin 100% : Filler 0%(A), Resin 90% : Filler 10% (B) Resin 80% : Filler 20%(C), Resin 70% : Filler 30%(D), Resin 60% : Filler 40% (E). Observed characteristics are kekutan composite tensile and impact strength. On average the highest tensile stress is the value obtained from the variation of the volume fraction of the specimen D (70% resin: 30% fiber) that is equal to 17.96 N/mm2, while the average value obtained from the lowest voltage variation of the volume fraction of the specimen B (90 % resin: 10% fiber) that is equal to 12:35 N/mm2. The average value of tensile strain obtained specimens A, B, C, D and E are the same, namely 0.68%. High MOE happens to specimens B, C and E, it indicates that the greater the value of the modulus of elasticity of the material is more difficult to increase the length, in this case the smallest specimen D modulus of elasticity. The average value of the energy required to break the specimen is equal to the highest Joule 34.728, obtained from the variation of the volume fraction of specimen D (70% resin: 30% fiber).